2014
DOI: 10.1183/09031936.00097014
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide levels found in infected cystic fibrosis sputum inhibit airway ciliary function

Abstract: We have previously reported cyanide at concentrations of up to 150 mM in the sputum of cystic fibrosis patients infected with Pseudomonas aeruginosa and a negative correlation with lung function. Our aim was to investigate possible mechanisms for this association, focusing on the effect of pathophysiologically relevant cyanide levels on human respiratory cell function.Ciliary beat frequency measurements were performed on nasal brushings and nasal air-liquid interface (ALI) cultures obtained from healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…In the current study, we focused on expanding our in vitro understanding of competitive interactions mainly mediated by cyanide that was recently proposed to be an important strategy used by P. aeruginosa to kill B. multivorans in LB co-cultures (Smalley et al, 2015 ). HCN is a poison produced by P. aeruginosa in the CF lung that can affect host immune functions (Anderson et al, 2010 ; Lenney and Gilchrist, 2011 ; Nair et al, 2014 ), with also the potential to outcompete other bacterial species in polymicrobial infections and consequently reduce species diversity of these complex communities. However, we showed that the competitive efficacy of P. aeruginosa toward the Bcc via the release of toxins, including cyanide, depends on several factors such as the growth medium, the in vivo adaptive evolution of P. aeruginosa , and the presence of other bacteria in the mixed community.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we focused on expanding our in vitro understanding of competitive interactions mainly mediated by cyanide that was recently proposed to be an important strategy used by P. aeruginosa to kill B. multivorans in LB co-cultures (Smalley et al, 2015 ). HCN is a poison produced by P. aeruginosa in the CF lung that can affect host immune functions (Anderson et al, 2010 ; Lenney and Gilchrist, 2011 ; Nair et al, 2014 ), with also the potential to outcompete other bacterial species in polymicrobial infections and consequently reduce species diversity of these complex communities. However, we showed that the competitive efficacy of P. aeruginosa toward the Bcc via the release of toxins, including cyanide, depends on several factors such as the growth medium, the in vivo adaptive evolution of P. aeruginosa , and the presence of other bacteria in the mixed community.…”
Section: Discussionmentioning
confidence: 99%
“…12 Additionally, Pseudomonas aeruginosa, a bacterium that causes ventilator-associated pneumonia and can be found in the lungs of cystic fibrosis patients, excretes cyanide in the form of hydrogen cyanide. 13 Oxidative phosphorylation is the most efficient metabolic pathway to generate ATP. In ciliated epithelial cells, ATP powers the coordinated action of multiple dynein motor proteins that drive ciliary beating.…”
Section: Redox Imaging and Optical Coherence Tomography Of The Respirmentioning
confidence: 99%
“…Recently, cyanide has been shown to impair mucociliary function in vitro [77]. G ilchrist et al [78] evaluated exhaled breath hydrogen cyanide (HCN) measured by SIFT (selected ion flow tube) mass spectrometry as a marker of P. aeruginosa infection in children.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…edwards et al [127], in a large cross-sectional survey of all surviving preterm-born children in Wales (n=13 361) and matched term control children, confirmed previous findings that preterm birth increases the risk of wheezing disorders [128]. Both the <5-year-old and 5–10-year-old preterm born children in the RANOPS had higher reported rates of wheezing ever, wheeze in the last 3 months and use of inhaled medication than term infants.…”
Section: Paediatric Respiratory Epidemiologymentioning
confidence: 99%